Pengaruh Kontrak Psikologis, Budaya Organisasi, Motivasi Kerja, dan Gaya Kepemimpinan Terhadap Kinerja Guru SMK Teknologi Balung Kabupaten Jember - Sulhan Ferdiansah; Hary Sulaksono; Lia Rachmawati (Bata Ilyas Educational Management Review, 2026)
Purpose: This study aims to analyze the influence of psychological contracts, organizational culture, work motivation, and leadership style on teacher performance at SMK Teknologi Balung, Jember Regency, both partially and simultaneously. The background of this study is based on the importance of improving teacher performance as a key factor in supporting the quality of education in vocational high schools. Research Design and Methodology: The research employed a quantitative method with a descriptive approach. The population consisted of 57 active teachers, with a sample of 40 respondents selected through simple random sampling. Data were collected using a Likert-scale questionnaire. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26, preceded by validity, reliability, and classical assumption tests. Findings and Discussion: The results indicate that psychological contracts, organizational culture, work motivation, and leadership style have a significant effect on teacher performance, both partially and simultaneously. Partially, organizational culture was found to be the most dominant variable affecting teacher performance, contributing 78.2%. Simultaneously, the four independent variables contributed 89.8% to teacher performance, while the remaining percentage was influenced by other factors outside the research model. Implications: The conclusion of this study confirms that improving teacher performance can be achieved through strengthening psychological contracts, fostering a positive organizational culture, increasing work motivation, and implementing effective leadership styles within the school environment